2013
DOI: 10.1186/1471-2296-14-193
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gaps: a qualitative study of perceptions of healthcare professionals on challenges and proposed remedies for cervical cancer help-seeking in post conflict northern Uganda

Abstract: BackgroundThere are limited data on perceptions of health professionals on challenges faced by cervical cancer patients seeking healthcare in the developing countries. We explored the views of operational level health professionals on perceived barriers to cervical screening and early help–seeking for symptomatic cervical cancer and the proposed remedies to the challenges.MethodsFifteen key informant interviews were held with health professionals including medical directors, gynecologists, medical officers, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(110 citation statements)
references
References 32 publications
4
103
2
1
Order By: Relevance
“…As it is generally needed a long time period for cancer development, so it is also generally preventable [32]. Several challenges face cervical cancer screening programs and help-seeking for cervical cancer in South Asia [33]. Despite the declining incidence of cervical cancer as a result of the introduction of screening programs, globally still now it remains a leading cause of cancer-related death in women [34].…”
Section: Introductionmentioning
confidence: 99%
“…As it is generally needed a long time period for cancer development, so it is also generally preventable [32]. Several challenges face cervical cancer screening programs and help-seeking for cervical cancer in South Asia [33]. Despite the declining incidence of cervical cancer as a result of the introduction of screening programs, globally still now it remains a leading cause of cancer-related death in women [34].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the reasons why cancer patients present to healthcare at a later stage in the LMICs than the high-income countries (HICs). In our recent Ugandan interview study, healthcare professionals suggested that advanced stage at diagnosis could be related to many challenges including patient factors such as inadequate awareness about cervical cancer symptoms, and healthcare factors such as inadequate skills to diagnose cervical cancer, inaccessibility of primary and secondary healthcare facilities, and a lack of specialized clinicians including pathologists and gynaecological oncologists [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…From our previous published observations, it was noted that some of the health care providers are not conversant with cancer symptoms and signs [17]. This is especially true for the lower carder/level health care providers who many times did not suspect cancer and were instead providing treatments for other ailments [35].…”
Section: Discussionmentioning
confidence: 99%